Answer:
The fifth term is -1/4.
Step-by-step explanation:
We know that the first three terms of the geometric sequence is <em>x, x</em> + 2, and <em>x </em>+ 3.
So, our first term is <em>x</em>.
Then our second term will be our first term multiplied by the common ratio <em>r</em>. So:
![x+2=xr](https://tex.z-dn.net/?f=x%2B2%3Dxr)
And our third term will be our first term multiplied by the common ratio <em>r</em> twice. Therefore:
![x+3=xr^2](https://tex.z-dn.net/?f=x%2B3%3Dxr%5E2)
Solve for <em>x</em>. From the second term, we can divide both sides by <em>x: </em>
![\displaystyle r=\frac{x+2}{x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20r%3D%5Cfrac%7Bx%2B2%7D%7Bx%7D)
Substitute this into the third equation:
![\displaystyle x+3=x\Big(\frac{x+2}{x}\Big)^2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%2B3%3Dx%5CBig%28%5Cfrac%7Bx%2B2%7D%7Bx%7D%5CBig%29%5E2)
Square:
![\displaystyle x+3 = x\Big( \frac{(x+2)^2}{x^2} \Big)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%2B3%20%3D%20x%5CBig%28%20%5Cfrac%7B%28x%2B2%29%5E2%7D%7Bx%5E2%7D%20%5CBig%29)
Simplify:
![\displaystyle x+3=\frac{(x+2)^2}{x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%2B3%3D%5Cfrac%7B%28x%2B2%29%5E2%7D%7Bx%7D)
We can multiply both sides by <em>x: </em>
![x(x+3)=(x+2)^2](https://tex.z-dn.net/?f=x%28x%2B3%29%3D%28x%2B2%29%5E2)
Expand:
![x^2+3x=x^2+4x+4](https://tex.z-dn.net/?f=x%5E2%2B3x%3Dx%5E2%2B4x%2B4)
Isolate the <em>x: </em>
![-x=4](https://tex.z-dn.net/?f=-x%3D4)
Hence, our first term is:
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
Then our common ratio <em>r</em> is:
![\displaystyle r=\frac{(-4)+2}{-4}=\frac{-2}{-4}=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20r%3D%5Cfrac%7B%28-4%29%2B2%7D%7B-4%7D%3D%5Cfrac%7B-2%7D%7B-4%7D%3D%5Cfrac%7B1%7D%7B2%7D)
So, our first term is -4 and our common ratio is 1/2.
Then our sequence will be -4, -2, -1, -1/2, -1/4.
You can verify that the first three terms indeed follow the pattern of <em>x</em>, <em>x</em> + 2, and <em>x</em> + 3.
So, our fifth term is -1/4.